2020
DOI: 10.1152/jn.00747.2019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically stimulating the lumbar region inhibits locomotor-like activity and increases the gain of cutaneous reflexes from the paws in spinal cats

Abstract: Mechanically stimulating the dorsal lumbar region inhibits locomotion and reduces weight support during standing in rabbits and cats. However, how this inhibitory effect from the lumbar skin is mediated is poorly understood. Here we evaluated the effect of mechanically stimulating (vibration or pinch) the dorsal lumbar region on short-latency (8- to 13-ms onset) cutaneous reflex responses, evoked by electrically stimulating the superficial peroneal or distal tibial nerves, in seven adult cats with a low thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…We also classified responses in contralateral muscles as P1 or N1 if the onset was ≤18 ms (Frigon & Rossignol, 2008;Hurteau et al, 2017;Merlet et al, 2020). In spinal cats, the longer-latency response (P2) starting at ~20-25 ms is small or absent (Frigon & Rossignol, 2008;Hurteau et al, 2017;Merlet et al, 2020). In the present study, we observed some P2 responses, in particular in IP and LG muscles, but not enough to perform statistical analyses.…”
Section: Reflex Analysis and Quantificationmentioning
confidence: 49%
See 4 more Smart Citations
“…We also classified responses in contralateral muscles as P1 or N1 if the onset was ≤18 ms (Frigon & Rossignol, 2008;Hurteau et al, 2017;Merlet et al, 2020). In spinal cats, the longer-latency response (P2) starting at ~20-25 ms is small or absent (Frigon & Rossignol, 2008;Hurteau et al, 2017;Merlet et al, 2020). In the present study, we observed some P2 responses, in particular in IP and LG muscles, but not enough to perform statistical analyses.…”
Section: Reflex Analysis and Quantificationmentioning
confidence: 49%
“…Interestingly, we reported that pinching the skin of the perineal region was more effective than vibration in decreasing the gain of cutaneous reflexes (Table 4). As the afferents activated by vibration and pinch differ (Merlet et al, 2020), we propose that the greater effect of pinch in decreasing the gain of short-latency cutaneous reflexes was due to the specificity of afferents involved (i.e., mainly cutaneous afferents).…”
Section: Perineal Stimulation Modulates Cutaneous Reflexes From Thementioning
confidence: 90%
See 3 more Smart Citations